Perspectives of a Sustainable Intercultural and Inclusive Education to Shape Life-Changers of Tomorrow - Presi, Olivera; Dervishaj, Adriana; La Ragione, Colomba (Journal of Education Culture and Society, 2024)
Aim. Reforming the HE Institutions in the context of integration requires new inputs in upgrading the curricula and adapting them to the needs of students for higher performance and productivity in all walks of life. The primary aim is to influence the policy agenda on sustainable education. Methods. Reinventing creative ways of teaching and learning, focusing on interdisciplinary and plurilingual modalities empowers students to think critically and solve daily problems by exploring and experimenting with digital techniques, thus promoting quality in teaching for academic success. Results. Plurilingual modalities and findings resulting thereof from the application of best practices will be carefully drafted through dedicated group projects to address the current problems for sustainable education. Challenges related to IT and education, whether the digital skills gap or the future of digital education, will also be at the forefront of the critical reflection. At the same time, it very much focuses on its mission to transform curricula and teaching methods towards sustainable education in the region and at large by organising dedicated workshops on sustainable development for students and teachers to better serve the respective communities and have a greater impact on our societies. Conclusions. Sustainable education means redefining the aim and impact of the interdisciplinary knowledge and results of teaching and learning by taking into account the needs of the job market and geopolitics.